Prediction of response to systemic treatment by kinetics of circulating tumor DNA in metastatic pancreatic cancer - Kirchweger, Patrick; Kupferthaler, Alexander; Burghofer, Jonathan; Webersinke, Gerald; Jukic, Emina; Schwendinger, Simon; Wundsam, Helwig; Biebl, Matthias; Petzer, Andreas; Rumpold, Holger (Frontiers in Oncology, 2022)
Introduction: Pretherapeutic detectable circulating tumor DNA (ctDNA) represents a promising prognostic biomarker for predicting relapse and overall survival in patients with metastatic pancreatic cancer. However, the prognostic value of ctDNA dynamics during treatment has not been studied thus far. We aimed to investigate the correlation between the change of ctDNA levels and response to treatment in patients treated by systemic therapy. Material and Methods: CtDNA detection using liquid biopsy (ddPCR utilizing KRAS G12/13 and, if negative, Q61 commercial test kits) was prospectively performed on patients with stage IV pancreatic cancer (i) prior to initiation of systemic chemotherapy and (ii) serially every two weeks until restaging. Detection rates, levels of ctDNA and the course of the relative ctDNA change (ctDNA kinetics) were correlated to treatment response and clinical outcome. Results: Detection rate at baseline was 64.3% (45/70) and complete serial measurement records were available for 32 ctDNA positive patients. Reduction of ctDNA levels below 57.9% of its baseline value at week 2 after treatment initiation was significantly predictive for response to treatment (AUC=0.918, sensitivity 91.67%, specificity 100%) and was associated with prolonged overall survival (OS) (5.7 vs. 11.4 months, p=0.006) and progression free survival (PFS) (2.5 vs. 7.7 months, p<0.000) regardless of treatment line. Pretherapeutic ctDNA detection was independently associated with worse OS in patients receiving first line regimen (7 vs. 11.3 months, p=0.046) and regardless of treatment line (11.4 vs. 15.9 months, p=0.045) as well as worse PFS (3.4 vs. 10.8 months, p=0.018). Conclusion: The change in magnitude of ctDNA during systemic treatment allows the prediction of treatment response and is associated with both, OS and PFS. This finding adds significant clinical potential to the already established prognostic value of ctDNA positivity in metastatic pancreatic cancer.